Effect of Filler Content on Properties of Asphaltic Mixtures for Marshall and Superpave Gyratory Compactor - Qasim, Zaynab Ibrahim; Abbas, Alaa Saadi; Qasim, Zahra Ibrahim (Al-Nahrain Journal for Engineering Sciences, 2017)
In Iraq some pavements of the newly constructed highway appear precocious distresses with unfavorable implications especially on the safety and the frugality. Cracking and permanent deformation are main types of these failures. The filler is doubtful to be a master contributor to these failures where its content has a significance effect on the mixture stiffness, and thereby affect the HMA pavement performance. The main objective of this research is to appreciate the influence of different contents of filler on the volumetric properties of asphaltic mixtures thus performance of asphalt mixtures through Comparative Evaluation between conventional Marshall Method and Super pave system. The implementation of a detailed experimental work is carried out to achieve the study objectives through the preparation of asphalt concrete samples using aggregate from Al-Nebaie quarry, (40-50) asphalt cement from Dourah refinery and limestone dust filler with four different contents of (0%, 4%, 8%, and 12%) by weight of the total aggregate. The volumetric properties for each mix design method are evaluated using Marshall Test and the Super pave Gyratory Compacter. The influence of filler contents on the rendering of these mixtures was evaluated.